Assessing the importance given by basketball coaches to training contents - Leite, N.; Coelho, E.; Sampaio, J. (Journal of Human Kinetics, 2011)
The purpose of this study was to compare the importance given by novice, intermediate and experienced basketball coaches to training contents. To achieve this purpose, a sample composed of Portuguese basketball coaches (n = 212) described how they rate the importance of technical, tactical, physical and drill contents. According to the results, there is a wide-ranging differential from novice to experienced coaches. First, while experienced coaches tend to focus on tactical development, novice and intermediate coaches seem to privilege the improvement of technical skills. Second, whereas significant differences between novice and intermediate coaches were found, evidence confirmed that they were higher (both in number and weight) when comparing experienced coaches against novice and intermediate. The study provided strong support to justify the necessity to adjust coaches` knowledge to players` biological developmental, and could form the basis of focused interventions in coaching development.